2014
DOI: 10.1021/ol501409a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Spirocyclized Indolenines via Palladium-Catalyzed Cascade Reactions of Tryptamine Derivatives and Propargyl Carbonate

Abstract: We report the intermolecular palladium-catalyzed reaction of tert-butyl propargyl carbonate with tryptamine derivatives or other indole-containing bis-nucleophiles. The reaction proceeds under mild conditions and with low catalyst loadings to afford novel spiroindolenine products in good to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 35 publications
6
39
0
Order By: Relevance
“…[106] Meanwhile, Rawal and co-workersr eported the reaction of av ariety of indole-tethered pro-nucleophiles, [Pd 2 (dba) 3 ], xantphos, and in some cases ab ase, to furnisha ni mpressive variety of spirocyclic indolenines 185/186,g enerally in good yield. [107] Recently,R awal and co-workersa lso described an asymmetric adaptation of this reaction, where in as imilar fashion to You and co-workers, chiral phosphine ligands( 188)w ere used to furnish the indolenines 189 in good to excellent yield and with high enantioselectivity. [108] Finally,L iu and co-workersd escribed an intriguing spirocyclisation methodology; [109] using ac hiral palladium complex with vinyl cyclopropane 194,ar eactive 1,3-dipole is formed in situ, which then undergoes af ormal [3+ +2]-cycloaddition with the b-unsaturated indolenine (afforded by the extrusion of phenyl sulfinic acid from sulfone 193)t of urnish the spirocycles 196.A range of substrates were well tolerated, generating spirocyclic indolenines as singled iastereoisomers, typically in good yield and with excellent enantioselectivity (Scheme 26).…”
Section: Additiont Op-allyl Intermediatesmentioning
confidence: 99%
See 2 more Smart Citations
“…[106] Meanwhile, Rawal and co-workersr eported the reaction of av ariety of indole-tethered pro-nucleophiles, [Pd 2 (dba) 3 ], xantphos, and in some cases ab ase, to furnisha ni mpressive variety of spirocyclic indolenines 185/186,g enerally in good yield. [107] Recently,R awal and co-workersa lso described an asymmetric adaptation of this reaction, where in as imilar fashion to You and co-workers, chiral phosphine ligands( 188)w ere used to furnish the indolenines 189 in good to excellent yield and with high enantioselectivity. [108] Finally,L iu and co-workersd escribed an intriguing spirocyclisation methodology; [109] using ac hiral palladium complex with vinyl cyclopropane 194,ar eactive 1,3-dipole is formed in situ, which then undergoes af ormal [3+ +2]-cycloaddition with the b-unsaturated indolenine (afforded by the extrusion of phenyl sulfinic acid from sulfone 193)t of urnish the spirocycles 196.A range of substrates were well tolerated, generating spirocyclic indolenines as singled iastereoisomers, typically in good yield and with excellent enantioselectivity (Scheme 26).…”
Section: Additiont Op-allyl Intermediatesmentioning
confidence: 99%
“…A similar strategy, which was developed around the same time by the You and Rawal groups, is the use of propargyl carbonates in intermolecular reactions; these reactions are proposed to proceed first by the interception of a typical η 3 ‐π‐allenylpalladium species by a nucleophile tethered onto the indole, before undergoing a protonation–spirocyclisation sequence to form the spirocyclic indolenine products (Scheme ). The contribution by You and co‐workers concerns the reaction of malonates 182 with methyl propargyl carbonate, [Pd 2 (dba) 3 ] and an appropriate phosphine ligand, to afford spirocyclic indolenines 183 in moderate to excellent yield, with preliminary results suggesting that an asymmetric variant is possible using ( R )‐segphos or related derivatives .…”
Section: Indole Dearomatisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, the Rawal group and we independently reported an intermolecular cascade dearomatization reaction of indole‐based bisnucleophiles with propargyl carbonate, leading to a series of spiroindolenines and spiroindolines. Moderate enantioselectivity (≤77 % ee ) was achieved for limited substrates (Scheme , reaction 1) . Rawal and co‐workers found that the indole N−H moiety could participate in the cyclization process when the nucleophilic side chain was decorated at the C2 position of the C3 methyl substituted indole (Scheme , reaction 2) .…”
Section: Figurementioning
confidence: 99%
“…The Rawal group extended this work to the dearomatization of tryptamine derivatives 123 (Scheme 27), 39 in which the nitrogen anion had undergone the initial attack, followed by spirocyclization to install the quaternary carbon center in 124. It can be postulated that the observed regioselectivity in products 124a-d arises from the lower pK a value of sulfonamides as compared to that of indoles.…”
Section: Scheme 16 Tandem Michael Addition / Cyclizationmentioning
confidence: 99%